Three-dimensional corrective exercise therapy for idiopathic scoliosis: study protocol for a prospective non-randomized trial - Zhou, Xuan; Li, Xin; Wu, Qikai; Liang, Juping; Guo, Haibin; Jin, Mengdie; Zhu, Xiaoqing; Du, Qing (BMC musculoskeletal disorders, 2022)
Although physiotherapeutic scoliosis-specific exercises (PSSEs) with or without other conservative treatments may improve scoliotic deformities, the evidence is insufficient. Three-dimensional corrective exercises (TDCEs) for scoliosis are based on the theory of PSSEs and are characterized by a combination of outpatient treatment and home-based exercise. This study aims to evaluate the effectiveness of TDCEs for idiopathic scoliosis (IS). The participants will be divided into two age- and sex-matched groups: an experimental group (EG) treated with three-dimensional corrective exercise therapy (TDCET) and a control group (CG) receiving generalized exercise therapy. In each arm, mild and moderate IS cases will be reclassified based on the Cobb angle and biopsy results. The primary endpoint is the change in the largest Cobb angle; the secondary endpoints are the sagittal index, forced vital capacity, peak oxygen uptake, and peak oxygen uptake. Sixty-six patients with mild IS and 78 patients with moderate IS will be included. This study is the first controlled trial to systematically assess the effectiveness of TDCEs for IS. In addition to TDCET including three-dimensional corrective exercises, family rehabilitation and basic body awareness therapy may help patients adopt supportive attitudes and appropriate behaviours, thus enhancing their compliance with exercises and achieving better outcomes. The study protocol was registered at www.clinicaltrials.gov (number identifier: NCT04539522 ). Registered on August 27, 2020.